Anti-inflammatory Effects of Lecania gerlachei Extract Collected from the Antarctic King Sejong Island - Min, Seul Ki; Kim, Jung Eun; Hong, Ju-Mi; Yim, Joung Han; Park, Hyun; Youn, Ui Joung; Han, Se Jong; Kim, Il-Chan (Biotechnology and bioprocess engineering, 2020)
Chronic inflammation is the cause of various diseases such as rheumatoid arthritis and asthma, with a large number of people suffering from them. There have been many reports that even link cancer to inflammation, so the development of sophisticated and powerful drugs continues to be in demand. Here we demonstrate that the methanol extract of Lecania gerlachei (LGME), a lichen member found in the extreme Antarctic environment, exhibits anti-inflammatory activities. Treatment of lipopoly-saccharide (LPS) stimulated Raw 264.7 murine macrophage cells with LGME reduced nitric oxide (NO) immune modulator production, and also down-regulated inducible nitric oxide synthase (iNOS), pro-inflammatory interleukin 6, 1ß and 1α (IL-6, IL-1ß and IL-1α), and tumor necrosis factor α (TNF-α) at both transcript and protein levels, in a concentration dependent manner. Furthermore, it was found that these effects were mediated by nuclear factor kappa B (NF-κB) signaling inhibition. Thus, our findings may contribute towards the development of novel inflammatory drugs.